Programmatic: Strategi Efektif Pemasangan Iklan Di Era Digital - Putra, Rakasiwi Permana; Irwansyah, Irwansyah (Jurnal Studi Komunikasi, 2021)
Programmatic Advertising (PA) is changing the way advertisers and publishers interact in the industrial 4.0. PA collects cookies from site pengguna to help advertisers identify the required audience. In PA, an important question is regarding the level of penetration and the reasons for using PA, especially in Indonesia. PA is different from traditional buying and selling advertising, which must bring together sellers and buyers face to face. Qualitative research is used in studying the situation based on the point of perspective of PA users with relevant backgrounds. Data collection techniques with interview observation using open coding, axial, and selective. Then, they used thematic and narrative data analysis with data confirmation through triangulation techniques in order to see data from various perspectives. As a result, in the Indonesian context, PA is growing well, it's just that it is still constrained by a complex implementation process (requires knowledge, insights, and networks).